Geography Matters in Ancient Greece - Melanie Waldron (Raintree, 2015)
How did a volcanic eruption put an end to Minoan civilization? What crops did the Ancient Greeks grow? How did city-states form around the Greek empire? Geography Matters in Ancient Greece looks at how the Greek Empire changed through time and gives fascinating insights into many different aspects of Greek life through its geography. Read about how the hot climate affected the crops that Greeks could grow and the housing and clothing they needed, how the Mycenaeans were able to protect themselves from attackers by using the natural features of their landscape and their natural resources of stone and how its proximity to the Mediterranean Sea helped the Greek Empire in trading and in strengthening their military might.
Keywords: Sustainable cities and communities; Non Fiction -- Non Fiction